EP644 Trends over time in use of primary and adjuvant hormonal therapy for endometrial cancer: a population based study. (1st November 2019) - van Weelden, WJ; Bretveld, R; van Erp, S; Engels, S; Romano, A; Massuger, L; Lalisang, R; Pijnenborg, J; van der Aa, M
Abstract : Introduction/Background: Endometrial cancer (EC) is the most common gynaecological cancer in the Western world with rising incidences due to increased life expectancy and obesity. As a result, EC is more frequently diagnosed among young patients and patients with high BMI and comorbidities. Many studies have confirmed the efficacy of hormonal therapy in young women who wish to preserve fertility, as alternative for surgical treatment. Yet, there are less data of hormonal therapy in elderly patients considered unfit for surgery. It is unclear whether the rising incidence of EC has influenced applied hormonal therapy over time. Therefore the aim of this study is to investigate trends in application of primary and adjuvant hormonal therapy in young and elderly patients. Methodology: Data of all patients diagnosed and treated for EC in the period 1989–2016 was extracted from the Netherlands Cancer Registry (NCR). Results: A total of 44.209 EC patients were included in the NCR, and analysed in four time periods. Primary hormonal therapy increased from 2.1% (n=184) to 2.7% (n=351), whereas the use of adjuvant hormonal therapy decreased from 2.3% (n=204) to 0.7% (n=91). Primary hormonal therapy among patients ≤40 years with FIGO stage I increased from 0% to 29%. The application of primary hormonal therapy also increased among patients >75 years for both FIGO stage I–II and FIGO stage III–IV disease (figure 1). Adjuvant systemic treatment for FIGO III–IV showed a decrease in hormonal therapy in favour of an increase in chemotherapy (figure 2). Conclusion: This study has shown that hormonal therapy is increasingly selected as primary therapy among patients ≤40 years and among patients >75 years old. In contrast, the use of adjuvant hormonal treatment has decreased at the cost of chemotherapy although the evidence for both treatments in this setting is limited. Disclosure: WJ van Weelden, R Bretveld, S van Erp, S Engels, LFAG Massuger, RI Lalisang, JMA Pijnenborg and MA van der Aa declare that there is no potential conflict of interest. A Romano was partly supported for this study by the Dutch Cancer Society (KWF Kankerbestrijding, www.kwf.nl), contract number UM-13-5782.